PATIENTS’ SATISFACTION WITH THE DENTAL CARE PROVIDED BY DENTAL STUDENTS - Habib, Syed Rashid; Ramalingam, Sundar; Beladi, Abdullah Al; Habib, Abdullah Al (Journal of Ayub Medical College Abbottabad, 2014)
Background: The success of an oral health service can be assessed by the degree of satisfaction of its patients. The objective of this study was to evaluate patient satisfaction following comprehensive dental treatment provided by final year dental students at college of dentistry, King Saud University, Riyadh, Saudi Arabia and to correlate the level of patient satisfaction with their post-treatment oral hygiene maintenance. Methods: The required information for this cross-sectional was collected from patients using a self-answered questionnaire. A five point Likert scale was used (Strongly agree, agree, neither, disagree and strongly disagree) to evaluate the level of patient satisfaction. Clinical examination included assessment of oral hygiene status using OHI-S (Oral Hygiene Index-Simplified). Results: Four hundred & forty-six patients who received comprehensive dental treatment at the student clinics during the past two years were contacted out of which 86 patient’s (81% males and 19% females) participated. The overall patient’s satisfaction score of 68.67±6.85 was highly satisfactory. The mean OHI-S score was 2.21±1.68. This showed a good to moderate level of oral hygiene among the participating patients. No statistically significant difference was found for the overall patient satisfaction score in relation to the age, gender, nationality and educational level. The post treatment oral hygiene status was significantly better in female patients compared to males. There was no statistically significant difference in OHI-S scores in relation to age, nationality and education level. The patient satisfaction scores and OHI-S score showed no correlation. Conclusion: The patients treated by the dental students at college of dentistry were highly satisfied with their treatment. A good to moderate level of post treatment oral hygiene among the participating patients was recorded according to the OHI-S. Keywords: Patient satisfaction; dental care; dental students; oral hygiene